Testing the Behavioral Life-Cycle Model fore Saving and Consumption. - Huang, Yanjun (2007)
Abstract The conflict between behavioral finance and standard finance came to the attention of economists since they recognized the importance of psychology in finance. This paper focuses on the empirical study of the behavioral life-cycle model that is a derivative model based on three concepts of behavioral finance, including self-control, mental accounting, and frame dependence. Through testing the differential marginal propensity to consume (MPC) hypothesis and the magnitude of the offset between pension saving and discretionary saving, the results show that the empirical evidence is more consistent with behavioral life-cycle theory.